Sobreposição de nicho de duas espécies simpátricas de Arthrosaura (Squamata: Gymnophthalmidae), na Floresta Nacional de Caxiuanã, Pará - SILVA, Kleiton Rodolfo Alves da (Universidade Federal do Pará, 2013)
In general, species with phylogenetic relationship use resources in similar ways and can be potential competitors. However, they can diverge in one of the three axis of the ecological niche; it may be at temporal axis, spatial and/or trophic axis. Those differences can be determinant for the existence of these populations. Assuming that these populations of Arthrosaura have had contact and that maybe has niche overlap, which strategies these species use to minimize the competition? Based on that, this study has the aim to investigate the spatial, temporal and trophic niche of these populations of Arthrosaura kockii e Arthrosaura reticulata in two sites at Caxiuanã’s National Forest. This is located between Melgaço and Portel county, Pará state, Brazil. Where were made three expeditions. The specimens were collected with the active search mode that began at 06:00 hours a.m and ended at 18:00 hours. Were collected data on 107 of A. kockii and 115 of A. reticulata of these, 107 and 113 had prey items in the digestive system, respectively. Stomachs were removed and the prey items were separated carefully and after were identified at the lowest taxonomic level. Were counted 26 prey items, which 25 were consumed by A. reticulata and 14 by A. kockii. Arthrosaura reticulata has a bigger niche breadth at the raining months and transitional months, A. kockii has a bigger niche breadth at the raining months and at drier months. The most important prey items consumed by A. reticulata were Araneae, Blattaria, Orthoptera-Gryllidae and Homopera, for A. kockii were Araneae, Blattaria, Orthoptera-Gryllidae and Isoptera. A. reticulata has a longer activity period initiating at 07: 50 am and ends at 5 pm, and has its peak of activity was between 09:00 hours and 14:30 hours. This specie was considered non-heliotherm. A. kockii had a smaller activity period, starting at 08:40 hours and ending at 15:25 hours and its peak of activity was between 10:00 hours and 14:30 hours. This specie was considered heliotherm. A. reticulata was found at the leaf litter with height between 2.5 cm and 13 cm, above and below this it was not found. A. kockii was found at the leaf litter with height between 1.5 cm and 10 cm, above and below those values it was not found. A. reticulata was found at many forest environments, near the water at low forest and at the terra firme forest, but A. kockii was only found at the terra firme forest. The deepness of the leaf litter and the distance from the water were important to the species distribution.